The Relation between Earnings Quality and Corporate Performance in a Transition Stock Market: the Portuguese Case - Rosário, J.; Annes, MC; Cristóvão, D.; Pinheiro, C. (XX Congresso AECA, 2019)
We use a sample of 46 non-financial firms, listed in the Lisbon Stock Exchange between 1987 and 2016 to examine the relation between the valuation of the firms and earnings attributes which reflect information quality to test whether the firms that present higher levels of information quality have greater valuation. We conduct this examination during a period in which the Portuguese stock market transitioned from an emerging marker classification into a developed market status in 1997. We Francis et al (2004) and define seven earnings attributes: Accrual Quality, Persistence, Predictability, Smoothness, Timeliness, Conservatism and Value Relevance. We test these measures against market valuation using Tobin’s Q measure and control the results for innate firm characteristics (firm size, capital structure, capital intensity, growth opportunities, insider ownership of shares and holding structures), as well as industry and year fixed effects. We test the impact of these earning attributes for the full sample as well as for the subsamples before and after the change market development status. The main results for the full sample are that only Persistence is statistically associated with greater firm valuation. The statistical significance of the predictability can be traced to period after the market status change.